2014
DOI: 10.1002/bse.1848
|View full text |Cite
|
Sign up to set email alerts
|

Has the CSR engagement of electrical companies had an effect on their performance? A closer look at the environment

Abstract: Even though electrical companies attain a top ranking in the publication of CSR reports, they are often accused of 'green-washing' due to their bad environmental reputation. The current economic crisis is testing their real CSR commitment more than ever, especially when this goes beyond its economic consequences.Based on a worldwide sample of electrical companies, we are going to study why companies are being socially responsible. We wish to know if it is due to the impact on the firms' performance or whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 79 publications
5
50
1
1
Order By: Relevance
“…For example, García‐Benau et al () found this positive relationship, when ROE was used as a measure of profitability. Miras‐Rodrígez, Carrasco‐Gallego, and Escobar‐Pérez () also found that when electric utility companies (in 26 different countries) took community‐oriented CSR actions, their profitability (ROA) increased.…”
Section: Literature Reviewmentioning
confidence: 93%
“…For example, García‐Benau et al () found this positive relationship, when ROE was used as a measure of profitability. Miras‐Rodrígez, Carrasco‐Gallego, and Escobar‐Pérez () also found that when electric utility companies (in 26 different countries) took community‐oriented CSR actions, their profitability (ROA) increased.…”
Section: Literature Reviewmentioning
confidence: 93%
“…() to examine the relationship between disclosed corporate responses to climate change and stock performance on the European and US stock markets or by Miras‐Rodríguez et al . () to examine the relationship between CSR and financial performance. To our best knowledge, it is the only publicly available database that provides non‐aggregate environmental data according to the four dimensions considered in our study (strategic intent, governance and management, engagement and operational performance).…”
Section: Methodsmentioning
confidence: 99%
“…Sustainability is referred to as the development that meets the needs of the present, without compromising the ability of future generations to meet their needs (Ali, Arafin, Moktadir, Rahman, & Zahan, ; Carter & Rogers, ; Dubey et al, ). Sustainability performances are based on investigating the potential negative impacts of economic activities on environments both in emerging and advanced economies (Miras‐Rodríguez, Carrasco‐Gallego, & Escobar‐Pérez, ; Welford & Gouldson, ). Organizational sustainability lies in the intersection of a firm's economic, environmental, and social performances (Rahdari & Rostamy, ; Rajesh, ).…”
Section: Literature Reviewmentioning
confidence: 99%